Shahan Perperyan's Work "The Two Times" inThe Context of Philosophical Reflections Concerning the Time - Petrosyan, Silva (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The article is dedicated to the critical analysis of the work "The Two Times" by Shahan Perperyan, one of the most interesting representatives of the Western Armenian philosophical thought of the 20th century. Perperyan's teaching about time has not yet been subject to historical-philosophical analysis, and the purpose of the article is to show the peculiarities of Perperyan's perception of time in the context of the history of philosophy. In order to do this, the views of Aristotle, Plotinus, Augustinos Aurelius, Kant and Bergson on time were presented and analyzed from the point of view of their relationship with Perperian's teaching. It has been shown that Perperian's approach essentially continues the line of Neo-Platonism, being particularly influenced by Bergson's consept of Duration.Perperian distinguishes between so-called "clock" or external and "musical" or internal times, giving preference to the latter. Internal time, according to him, has the possibility of having in it collective spirituality at once. Perperyan shows that thanks to the ability to endure, a person gains creative freedom and can shape not only his future, but also his past. Similarly, according to the Western Armenian thinker, a people becomes a nation when it raises its existence and being to a spiritual level. The nation, constructing its history, becomes a "collective personality", liberating its outwardly transitory and erasing life from the erasing course of external time and establishing it in the collective internal dense Duration.Perperyan connects the mastery of inner time with the presence of the soul, sanctity. He notes that people misunderstand eternity, thinking that it will come at the end,and waiting for it. But a blessed, holy person is already living in eternity, because he carries all the times within him.
Keywords: “clock” time; “musical” time; Inner time; Duration; Perperyan, Bergson; Augustine; Kant.